Broadband near-infrared (NIR) emission realized by the crystal-field engineering of Y3−xCaxAl5−xSixO12:Cr3+ (x = 0–2.0) garnet phosphors. Issue 6 (6th January 2020) - Mao, Minqian; Zhou, Tianliang; Zeng, Huatao; Wang, Le; Huang, Fan; Tang, Xueyuan; Xie, Rong-Jun
Abstract : Broadband NIR emission with high IQE was realized by crystal-field engineering of Y2 CaAl4 SiO12 :Cr. Abstract : The rapid development of portable spectrometers has evoked a large demand for minimized light sources; meanwhile, NIR phosphor-converted light-emitting diodes (NIR pc-LEDs) are an optimal choice due to their compactness and low cost. The phosphors used in NIR spectroscopy (NIRS) are required to have broadband emission and high quantum efficiency (QE) for a wider detection range and efficient photo-to-electricity conversion. Inspired by the structural tunability of Y3 Al5 O12 (YAG), we proposed to achieve broadband emission by crystal field engineering, i.e., indirectly regulating the crystal field strength of Cr 3+ via the co-substitution of Y 3+ –Al 3+ by Ca 2+ –Si 4+ in YAG. The crystal field strength experienced on Cr 3+ decreased as the octahedron was distorted and enlarged by the co-substitution. A broadband NIR emission with a large full width at half maximum (FWHM) of 160 nm and a high internal quantum efficiency (IQE) of ∼75.9% was realized in Y3− x Ca x Al5− x Si x O12 :0.6% Cr ( x = 1). The suitability of the investigated NIR phosphor was demonstrated by fabricating an NIR pc-LED prototype, and the detection resolution was improved by 30% compared to that of a traditional white pc-LED. These results indicate the great potential of the Y2 CaAl4 SiO12 :Cr phosphors for use in highly precise and sensitive NIR pc-LEDs.